Gestión de Planificación de actividades en el Departamento de Salud Ocupacional del Municipio de Babahoyo - Sotomayor Erazo, Wladimir José (2020)
Planning is an important process for an organization, since it is the first activity that helps to achieve the objectives and the success of the other administrative activities depends on its adequate elaboration and execution. The research was carried out with the objective of knowing the problems presented in the Occupational Health department related to the planning of its activities and its consequences for not considering unforeseen scenarios such as cancellation of medical brigades, winter season or lack of resources, among others, that affect your services. To achieve this objective, a survey and interview were applied to the six employees and the head of the department, respectively. By applying these tools, it is concluded that the problems generated by not carrying out adequate planning prevent achieving a higher level of satisfaction for users of the Municipality of Babahoyo Canton, it is evident that there is poor coordination between departments, lack of resources, internal conflicts, erroneous homework assignment, poor internal communication.